Birth Weight and Adult Obesity Index in Relation to the Risk of Hypertension: A Prospective Cohort Study in the UK Biobank - Zhang, Yi; Liang, Jingjia; Liu, Qian; Fan, Xikang; Xu, Cheng; Gu, Aihua; Zhao, Wei; Hang, Dong (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To investigate the association between birth weight and risk of hypertension, and to examine the interaction between birth weight and adult obesity index. Methods: We included 199,893 participants who had birth weight data and no history of hypertension at baseline (2006-2010) from UK Biobank. A multivariate cubic regression spline was used to visually explore the dose-response relationship. Multivariate Cox proportional hazards regression models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: We observed a non-linear inverse association between birth weight and hypertension. The risk for hypertension decreased as birth weight increased up to approximately 3.80 kg. Compared to the participants with the fourth quintile of birth weight (3.43-3.80 kg), those with the first quartile of birth weight (<2.88 kg) were associated with a 25% higher risk of hypertension [HR 1.25; 95% CI (1.18-1.32)]. In addition, the participants with birth weight <2.88 kg and body mass index ≥30 kg/m2 had the highest risk [HR 3.54; 95% CI (3.16-3.97); P for interaction <0.0001], as compared to those with birth weight between 3.43-3.80 kg and body mass index between 18.5-25.0 kg/m2. These associations were largely consistent in the stratified and sensitivity analyses. Conclusion: Our findings indicate that lower birth weight is non-linearly associated with higher risk of hypertension, and birth weight between 3.43-3.80 kg might represent an intervention threshold. Moreover, lower birth weight may interact with adult obesity to significantly increase hypertension risk.